Molecular biology in medicinal chemistry - Dingermann, Theodor; Steinhilber, Dieter, 1959-; Folkers, Gerd. (Weinheim : Wiley-VCH, 2004)
Explains the identification of molecular targets via cellular assays, reporter genes or transgenic models, as well as surveying recent advances in the synthesis, separation and analysis of drugs. A special section is devoted to molecular genetics methods. Appropriate for pharmaceutical chemists, molecular biologists and medical researchers using molecular methods to study drugs and their action
Cellular assays in drug discovery -- Gene knockout models -- Reporter gene assay systems for the investigation of GPCRs -- From the human genome to new drugs: The potential of orphan GPCRs -- Stereoselective synthesis with the help of recombinant enzymes -- Nucleic acid drugs -- Recent trends in enantioseparation of chiral drugs -- Affinity chromatography -- NMR-based drug discovery -- 13C- and 15N-Isotopic labeling of proteins -- Antibody fragments as crystallization enhancers -- Pharmacogenetics: the effect of inherited henetic variation on drug disposition and drug response -- Pharmacogenomics of bioavailability and elimination -- Toxicogenomics: integration of new molecular biological tools in toxicology
Keywords: Chemistry, Pharmaceutical; Genetic engineering; Molecular biology